Effect of Non-pharmaceutical Interventions on COVID-19 in Rwanda: An Observational Study - Edson Rwagasore; Olivier Nsekuye; Alfred Rutagengwa; Ziad El-Khatib (Springer, 2023)
Abstract Background On 11 March 2020, COVID-19 was declared as a pandemic by the World Health Organization (WHO). The first case was identified in Rwanda on 24 March 2020. Three waves of COVID-19 outbreak have been observed since the identification of the first case in Rwanda. During the COVID-19 epidemic, the country of Rwanda has implemented many Non-Pharmaceutical Interventions (NPIs) that appear to be effective. However, a study was needed to investigate the effect of non-pharmaceutical interventions applied in Rwanda to guide ongoing and future responses to epidemics of this emerging disease across the World. Methods A quantitative observational study was conducted by conducting analysis of COVID-19 cases reported daily in Rwanda from 24 March 2020 to 21 November 2021. Data used were obtained from the official Twitter account of Ministry Health and the website of Rwanda Biomedical Center. Frequencies of COVID-19 cases and incidence rates were calculated, and to determine the effect of non-pharmaceutical interventions on changes in COVID-19 cases an interrupted time series analysis was used. Results Rwanda has experienced three waves of COVID-19 outbreak from March 2020 to November 2021. The major NPIs applied in Rwanda included lockdowns, movement restriction among districts and Kigali City, and curfews. Of 100,217 COVID-19 confirmed cases as of 21 November 2021, the majority were female 51,671 (52%) and 25,713 (26%) were in the age group of 30-39, and 1866 (1%) were imported cases. The case fatality rate was high among men (n = 724/48,546; 1.5%), age > 80 (n = 309/1866; 17%) and local cases (n = 1340/98,846; 1.4%). The interrupted time series analysis revealed that during the first wave NPIs decreased the number of COVID-19 cases by 64 cases per week. NPIs applied in the second wave decreased COVID-19 cases by 103 per week after implementation, while in the third wave after NPIs implementation, a significant decrease of 459 cases per week was observed. Conclusion The early implementation of lockdown, restriction of movements and putting in place curfews may reduce the transmission of COVID-19 across the country. The NPIs implemented in Rwanda appear to be effectively containing the COVID-19 outbreak. Additionally, setting up the NPIs early is important to prevent further spread of the virus.